TRADE-OFF IN CONSUMPTION OF IMPORTED AND TRADITIONAL OWN FOODS AMONGST IGBO FARM HOUSEHOLDS IN NIGERIA - Christopher Ogbonna EMEROLE; Chima Innocent EZEH; Obioha OKORIE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Changing demand against locally produced foods amongst Igbo farm households in South-eastern Nigeria is in the increase. Food items such as rice, fish, and poultry products are among imported foods that presently challenge consumer preferences. It is pertinent across farm household ages and income groups to determine factors that inform trade-off in consumption of imported foods which types are locally produced. A survey of the core Igbo states was carried out following a multi-stage cluster sampling method that selected five of the seven States that are traditional home of the Igbos. A total of 480 farm households were chosen as panel of respondents from whom socio-economic and food consumption information was gathered using a mixture of methods. Data on protein and carbohydrate intakes were gathered by interviewing each household member except infants on the food consumed on a 48–hour-recall approach. The analysed data revealed that foods produced included roots, tubers, cereals, legumes, fats and oil, fish, meat, eggs, fruits, vegetables, and spices. There were significant differences between value of annual per capita nutrition gaps in intake of energy foods and protein (respectively) by Children, Adolescents and Adults in the farm households. The age of the household head was a factor that positively favoured consumption of own foods against their imported brands. The study recommended that households should patronize own products and call for change of tastes, preferences and value as well as adjust their production plans to produce more legumes in their product mix.